2016
DOI: 10.1088/0963-0252/25/2/025026
|View full text |Cite
|
Sign up to set email alerts
|

Development and studies on a compact electron cyclotron resonance plasma source

Abstract: It is well known that electron cyclotron resonance (ECR) produced plasmas are efficient, high-density plasma sources and have many industrial applications. The concept of a portable compact ECR plasma source (CEPS) would thus become important from an application point of view. This paper gives details of such a CEPS that is both portable and easily mountable on a chamber of any size. It uses a fully integrated microwave line operating at 2.45 GHz, up to 800 W, cw. The required magnetic field is produced by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
(41 reference statements)
1
19
0
Order By: Relevance
“…An indigenously developed electronic circuit and LABVIEW-based program were used to record the I-V characteristics for both, the discharge (V d -I d ) and the LP. The procedure for the analysis of the LP data and determination of the plasma parameters used in the present work has already been discussed in great detail in the appendix of an earlier paper by the authors [14] and can also be found elsewhere [15,[29][30][31][32]. Therefore, the LP analysis method will not be presented here.…”
Section: Diagnostics: Langmuir Probementioning
confidence: 99%
“…An indigenously developed electronic circuit and LABVIEW-based program were used to record the I-V characteristics for both, the discharge (V d -I d ) and the LP. The procedure for the analysis of the LP data and determination of the plasma parameters used in the present work has already been discussed in great detail in the appendix of an earlier paper by the authors [14] and can also be found elsewhere [15,[29][30][31][32]. Therefore, the LP analysis method will not be presented here.…”
Section: Diagnostics: Langmuir Probementioning
confidence: 99%
“…For non-magnetized high frequency plasmas, the relative permeability µ p r = 1. The density of the abosrbed power from the electromagnetic is calculated as in the following equation [1,[46][47][48][49].…”
Section: The Electromagnetic Field Modelmentioning
confidence: 99%
“…Before describing the experimental system, it is worth dwelling upon the structure of the magnetic eld inside the CEPS. The CEPS itself is described in detail in reference [27] and shown in gure 1(a). The microwave launcher, the impedance matching unit and mode converter all form an integral part of the CEPS that allow coupling of CW microwaves (2.45 GHz, 200-600 W) into the plasma source section (PSS) through a quartz window.…”
Section: Ceps Magnetic Fieldmentioning
confidence: 99%
“…Some preliminary studies using these sources have also been undertaken. The CEPS has been used singly as a standalone source by attaching it to a small chamber [27,28]. Multiple CEPS (up to 12 in number) have also been used for lling a very large volume system [29,30] (∼1.7 m 3 ; dia ≈ 1 m) with high density, highly uniform plasma using very modest microwave power in each CEPS.…”
Section: Introductionmentioning
confidence: 99%